Alkalicella caledoniensis gen. nov., sp. nov., a novel alkaliphilic anaerobic bacterium isolated from 'La Crouen' alkaline thermal spring, New Caledonia. Issue 5 (18th May 2021) - Quéméneur, Marianne; Erauso, Gaël; Bartoli, Manon; Vandecasteele, Céline; Wils, Laura; Gil, Lisa; Monnin, Christophe; Pelletier, Bernard; Postec, Anne
Abstract : A novel anaerobic, alkaliphilic, mesophilic, Gram-stain-positive, endospore-forming bacterium was isolated from an alkaline thermal spring (42 °C, pH 9.0) in New Caledonia. This bacterium, designated strain LB2 T, grew at 25–50 °C (optimum, 37 °C) and pH 8.2–10.8 (optimum, pH 9.5). Added NaCl was not required for growth (optimum, 0–1 %) but was tolerated up to 7 %. Strain LB2 T utilized a limited range of substrates, such as peptone, pyruvate, yeast extract and xylose. End products detected from pyruvate fermentation were acetate and formate. Both ferric citrate and thiosulfate were used as electron acceptors. Elemental sulphur, nitrate, nitrite, fumarate, sulphate, sulfite and DMSO were not used as terminal electron acceptors. The two major cellular fatty acids were iso-C15 : 0 and C16 : 0 . The genome consists of a circular chromosome (3.7 Mb) containing 3626 predicted protein-encoding genes with a G+C content of 36.2 mol%. Phylogenetic analysis based on the 16S rRNA gene sequence indicated that the isolate is a member of the family Proteinivoraceae, order Clostridiales within the phylum Firmicutes . Strain LB2 T was most closely related to the thermophilic Anaerobranca gottschalkii LBS3 T (93.2 % 16S rRNA gene sequence identity). Genome-based analysis of average nucleotide identity and digital DNA–DNA hybridization of strain LB2 T with A. gottschalkii LBS3 T showed respective values of 70.8 and 13.4 %. Based on phylogenetic, genomic, chemotaxonomic and physiological properties, strain LB2 T is proposed to represent the first species of a novel genus, for which the name Alkalicella caledoniensis gen. nov., sp. nov. is proposed (type strain LB2 T =DSM 100588 T =JCM 30958 T ).